The joy of eating : a guide to food in modern pop culture - Glenn, Jane K. (Santa Barbara, California : ABC-CLIO, 2022)
"This volume explores our cultural celebration of food, blending lobster festivals, politicians' roadside eats, reality show "chef showdowns," and gravity-defying cakes into a deeper exploration of why people find so much joy in eating"--
"In 1961, Julia Child introduced the American public to an entirely new, joy-infused approach to cooking and eating food. In doing so, she set in motion a food renaissance that is still in full bloom today. Over the last six decades, food has become an increasingly more diverse, prominent, and joyful point of cultural interest. The Joy of Eating discusses in detail the current golden age of food in contemporary American popular culture. Entries explore the proliferation of food-themed television shows, documentaries, and networks; the booming popularity of celebrity chefs; unusual, exotic, decadent, creative, and even mundane food trends; and cultural celebrations of food such as festivals and mascots and in music. The volume provides depth and academic gravity by tying each entry into broader themes and larger contexts-in relation to a food-themed reality show, for example, discussing the show's popularity in direct relation to a significant economic event, providing a brief history behind popular foods and types of cuisines, and tracing the evolution of our understanding of diet and nutrition, among other explications"--
All-star chef classic -- America's test kitchen -- Art, food in (antiquity through the Renaissance) -- Art, food in (impressionism through contemporary art) -- Asian American cuisine -- Aspen food and wine classic -- Austin food + wine festival -- Ayden collard festival -- Baby food -- Bar rescue -- Barbecue -- Batali, Mario -- Bayless, Rick -- Beard, James -- Best thing I ever ate, The -- Bizarre foods with Andrew Zimmern -- Bourdain, Anthony -- Brown, Alton -- Cake and cupcake trends -- California avocado festival -- Celebrities and food -- Chang, David -- Chef's table -- Child, Julia -- Chocolate events and destinations -- Chopped -- Coffee culture -- Cooked -- Cooks vs. Cons -- Craft brewing and microbreweries -- Culinary awards, The evolution of -- Deen, Paula -- Deer River wild rice festival -- Documentary films, food and beverages in -- Eating competitions -- Farmhouse rules -- Fiction, Food in -- Fictional television (1950s-1970s), Food and -- Fictional television (1980s-), Food and -- Fieri, Guy -- Films, Food in -- Flay, Bobby -- Florida Strawberry Festival -- Food and beverage museums, International -- Food and beverage museums, U.S. -- Food failures -- Food trucks -- Galloping gourmet, The -- Garten, Ina -- Gilroy Garlic Festival -- Great British bake off, The -- Grilled cheese festivals -- Hazan, Marcella -- Holidays and food -- Ice cream trends -- Imagery found in foods -- International Horseradish Festival -- Iron chef -- Lagasse, Emeril -- Latin American cuisine -- Laurentiis, Giada De -- Magazines, Food -- Maine Lobster Festival -- Maple syrup festivals -- MasterChef -- Mind of a chief, The -- Nonfiction, Food in -- Novelty dining experiences -- Pépin Jacques -- Photography, Food -- Pioneer woman, The -- Politicians' food gaffes -- Politics and food -- Puck, Wolfgang -- Radio and podcasts, Food-themed (1920s-1970s) -- Radio and podcasts, Food-themed (1980s-) -- Ramsay, Gordon -- Ray, Rachael -- Roadside food attractions -- Samuelsson, Marcus -- Sherman, Sean -- South Beach Wine & Food Festival -- Spam Jam Festival -- Stewart, Martha -- Super Bowl Sunday -- Super size me -- Taste of Chicago -- Television, Food channels on -- Top chef -- Tosi, Christian -- Trends, Food -- Twitty, Michael -- Two fat ladies -- Unusual food events, International -- Unusual food events, U.S. (Midwest, West, and Southwest Regions) -- Unusual food events, U.S. (Southeast and Northeast Regions) -- Unusual foods -- Websites, Food -- What the fluff? -- Wine and spirits -- Worst cooks in America.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 29, 2021).
eBooks on EBSCOhost
Keywords: Food -- United States -- History; Food habits -- Social aspects -- United States; Food in popular culture -- United States; Aliments -- États-Unis -- Histoire; Habitudes alimentaires -- Aspect social -- États-Unis.; Aliments dans la culture populaire -- États-Unis.; SOCIAL SCIENCE / Agriculture & Food (see also POLITICAL SCIENCE / Public Policy / Agriculture & Food Policy); SOCIAL SCIENCE / Popular Culture; Food; Food habits -- Social aspects; Food in popular culture; United States; History